Poststroke Hip Fracture: Prevalence, Clinical Characteristics, Mineral-Bone Metabolism, Outcomes, and Gaps in Prevention. (25th September 2013) - Fisher, Alexander; Srikusalanukul, Wichat; Davis, Michael; Smith, Paul
Abstract : Objective . To assess the prevalence, clinical and laboratory characteristics, and short-term outcomes of poststroke hip fracture (HF). Methods . A cross-sectional study of 761 consecutive patients aged ≥60 years (82.3 ± 8.8 years; 75% females) with osteoporotic HF. Results . The prevalence of poststroke HF was 13.1% occurring on average 2.4 years after the stroke. The poststroke group compared to the rest of the cohort had a higher proportion of women, subjects with dementia, history of TIA, hypertension, coronary artery disease, secondary hyperparathyroidism, higher serum vitamin B12 levels (>350 pmol/L), walking aid users, and living in residential care facilities. The majority of poststroke HF patients had vitamin D insufficiency (68%) and excess bone resorption (90%). This group had a 3-fold higher incidence of postoperative myocardial injury and need for institutionalisation. In multivariate analysis, independent indicators of poststroke HF were female sex (OR 3.6), history of TIA (OR 5.2), dementia (OR 4.1), hypertension (OR 3.2), use of walking aid (OR 2.5), and higher vitamin B12 level (OR 2.3). Only 15% of poststroke patients received antiosteoporotic therapy prior to HF. Conclusions . Approximately one in seven HFs occurs in older stroke survivors and are associated with poorer outcomes. Early implementation of fracture prevention strategies is needed.